Forming Critical Character With Higher Order Thinking Skill (HOTS) Based Learning Assessment in Islamic Religious Education Subjects - Cecep Sobar Rochmat; Syifa Rizki Sholihah; Shofia Niswah Qonita (Educan : Jurnal Pendidikan Islam, 2022)
Character formation is one of the goals of education, especially Islamic education. One important character is a critical character. Critical is a character that is commonly owned by students, the formation of this character is seen from the ability of students to analyze various kinds of problems sharply and deeply. The purpose of this study is to reveal that in developing the critical thinking character of students, it is necessary to apply a learning assessment based on High Order Thinking Skills (HOTS). HOTS-based assessment is an assessment based on questions compiled by the teacher to measure the ability of students in the realm of analysis, evaluation, and creativity. The method used in this research is library research method using a descriptive approach. The results of this study are in the form of concepts used in HOTS-based assessments, as well as their implementation in PAI subjects. Not only that, the competence of a PAI teacher in the application of the HOTS-based assessment concept is very influential, so that the HOTS-based assessment is able to form a critical character in students.